CONTACTLESS ROBOT FOR VIRUS ATTACKED HOSPITALIZED PEOPLE (International Journal of Food and Nutritional Sciences, 2023)
This project describes the evolving role of robotics in healthcare and allied areas with special concerns relating to the management and control of the spread of the novel coronavirus disease 2019 (COVID-19). The prime utilization of such robots is to minimize person-to-person contact and to ensure cleaning, sterilization and support in hospitals and similar facilities such as quarantine. The Robot measure the Body Temperature and Heartbeat of the patient. This will result in minimizing the life threat to medical staff and doctors taking an active role in the management of theCOVID-19 pandemic.